Satisfacción de los usuarios externos del servicio de consulta externa del hospital de apoyo “Elpidio Berovides Pérez” Otuzco, La Libertad marzo-abril 2016 - Zavaleta Rodriguez, Marianelly Estefany (2016)
The objective of this research was to determine the satisfaction degree of external users treated in the external consultation of the Hospital de Apoyo "Elpidio Pérez Berovides" Otuzco, La Libertad, in the months March and April 2016. The probabilistic sample consisted of 141 external users from 18 to 70 years old, intentionally selected. The study design was descriptive, prospective and transversal. The Service Quality (SERVQUAL) questionnaire, modified and validated by Cabellos E. y Chirinos J in 2011 was used as an instrument to measure the user satisfaction level. The results show a low degree of global satisfaction represented by 63.11% of users dissatisfied. Dissatisfaction was found in all dimensions being highest in Responsiveness (66.31 %), Tangibility (65.07%) and Reliability (64.68%). The main dissatisfaction variables were the poor availability and easiness to get an appointment (73.76%) and the delay in radiological examinations (69.50%). The dimension of quality with the greatest relative importance for the users was Tangible Aspects (23.33%). However, the Empathy dimension had the highest correlation with the global satisfaction level: Pearson correlation coefficient (r = 0.900) and it is statistically meaningful (p<0.01).